A new species of Chiloschista (Orchidaceae, Aeridinae) from northern Vietnam - Pham, Phuoc Dien; Averyanov, Leonid V.; Nguyen, Dinh Hiep; Maisak, Tatiana; Nguyen, van Canh; Dang, Minh Quan; Truong, Ba Vuong; Dang, van Son (Phytotaxa, 2022)
A yellow-flowered Chiloschista (Orchidaceae, Aeridinae) with brown-spotted tepals is described as a new species. It was initially collected in Son La Province, Thuan Chau District, and later flowered in cultivation when it was identified as a new specie. This new species resembles C. parishii and C. himalaica in habit, shape and color of the flower, but differs from C. parishii and C. himalaica by glabrous sepals and lip ornamentation characters. The paper includes the standard description, the plate with analytical photos, data on habitat, phenology, and conservation status of the new species.